"I Knew I Was Making a Difference": - Victoria Frank; Rekha Shukla; Barbara Goldberg (Journal of College Orientation, Transition, and Retention, 2025)
Early college high schools (ECHSs) are designed to improve the postsecondary outcomes of historically marginalized students in higher education. ECHS graduates are the target population for an innovative scholarship and support program, the Greater Texas Foundation Scholars Program (GTF Scholars), that has operated at several public universities in Texas for over a decade. We examine the perspectives of the GTF Scholars Program Coordinators who implement the core elements of the program. Coordinators share their views about GTF Scholars — from their strong potential to the stumbling blocks they can face. The coordinators share the strategies that they have developed and used to support this unique group of students. This article offers best practices useful to any institutions seeking to improve their support for ECHS graduates.